بلاغة الصورة في تلقي "ظاهرة اختطاف الأطفال بالجزائر" : قراءة سيميائية لنماذج من الصور الصحفية - ثابت، طارق (جامعة باتنة, 2019)
Every discourse yields a meaning to transmit. Given that the image is a discourse, it consists a subject to this rule; framed with two contexts: Production and reception. Considering that the discourse of “The prevention of child kidnapping phenomenon” is based on the attempt of eliminating an outsider phenomenon in the Algerian Society, It’s strategy believes in that cognitive faith in philosophy of life and existence, in all of its dimensions, generating such a sentimental feeling which is issued from the project of the image, and admitting the fact of communicating the other, according the communicative ways required by the advertising aim, which put into account both: the persuasion and the persuasive competency, as a source of the analytic creative action. Therefore, in the light of this study, we will use the rhetorical semantic method, as the most appropriate, to address the reception of the press releases, that is linked to the to the projects of the state, the Algerian media and civil society, concerning the rejection and fight against this phenomenon, as well as the investigation of its rhetorical devices, according to Barthes’s view, which helps in interpreting the possible meanings its signs can convey, through the presentation of analytic models excerpt from Algerian and Arab magazines and newspapers.
إن أي خطاب ينتج معنى ما يستهدف إبلاغه، وكون الصورة خطابا، فهي خاضعة لهذه القاعدة مؤطرة بسياقين: الإنتاج والتلقي، ولئن كان الخطاب حول "مناهضة ظاهرة اختطاف الأطفال بالجزائر" ينبني على محاولة القضاء على ظاهرة دخيلة في بنية المجتمع الجزائري، فإن استراتيجيته تؤمن بذلك الإيمان المعرفي بفلسفة الحياة والوجود في شتى أبعادها ليتولد ذلك الإحساس الوجداني المنحدر من مشروع الصورة يقر بحقيقة التواصل مع الآخر وفق ما تقتضيه الغاية الإشهارية انطلاقا من سبل تواصلية تضع كلا من الإقناع والكفاءة الإقناعية في الحسبان كونها منطلق الفعل التحليلي المبتكر. ولهذا سنعتمد في ضوء هذه الدراسة المنهج البلاغي السيمائي - باعتباره الأنسب - لتناول تلقي الصورة الصحفية المتعلقة بمشاريع الدولة والمجتمع المدني والإعلامي الجزائري في رفض هذه الظاهرة ومحاربتها وتقصي أوجه بلاغتها وفق الرؤية البارثية التي تعين على تأويل ما يمكن أن تؤديه علاماتها من معان من خلال عرض نماذج تحليلية من مجلات وجرائد جزائرية وعربية.
Keywords: الصورة الصحفية -- بلاغة الصورة -- السيميائية -- جريمة اختطاف الأطفال -- الجزائر